ANALISIS STATUS IUU FISHING DI PELABUHAN PERIKANAN PANTAI BANDA KABUPATEN MALUKU TENGAH - Tuhumena, Lolita Constantia; A. Tomasila, Leopold; Talakua, Eygner Gerald (Universitas Pattimura, 2025)
Functions of a fishing port as a place for supervision and fish resource control. In the context of prevention and IUU fishing controll, surveillance at fishing ports needs attention for evaluation. After that, research about prevention and IUU fishing control still resting on legal aspects study and policy analysis published. This research done to evaluate prevention and IUU fishing control especially in Banda Beach Fisheries Port, Maluku Province in the context of supervising the management of fish resources in WPP 714. The research done on Banda Coastal Fisheries Port (PPP), Banda District, Central Maluku Regency from June-November 2021. Descriptive analysis for analyze the data with method decription or describe the data that has been collected as it is without means to draw applicable conclusions for general (Sugiyono,2018). This analyze used index analyzes, for get tendency of answers from respondents to each variable. This study shows that IUU Fishing status in a moderate state (1,9) with the components that make up the index are 3 (three) i.e. iIlegal, Unreported and Unreported is moderate (1,9). The variables with the highest level of compliance are Unreported (2,1), then Ilegal (1,9) and Unregulated (1,7).